Chemical and Antimicrobial Studies on the Skin of Aloe indica Leaves at Different Ages of Plants - Jahan, Ismet Ara; Tarek, Fakir Shahidullah; Islam, M Shahidul; Chowdhury, Jasim Uddin; Begum, Fawzia; Sattar, M Abdus (Bangladesh Journal of Scientific and Industrial Research, 2009)
A comparative study on mineral profile, water content, solid content and ash contents were done on the skin of the leaves at three different ages of Aloe indica plants. Fatty acid analysis and screening of antibacterial sensitivity against two bacteria were also carried out. Mineral profile was evaluated by Atomic absorption spectrophotometer and Flame photometer. Whereas the esterified fatty extract analysis was done by GC/MS spectrophotometer. Sodium, potassium, magnesium and calcium were found to be present as major minerals whereas zinc, copper, silver, phosphorous, chromium were found as trace elements. No arsenic was found to be present in any of the samples. The amount of different mineral contents exists in the order of 1 year < 2 years> 3 years. A comparative study of the mineral contents of the skin with the fillet was also done. Percent compositions of the fatty acid contents were found to be very different in different maturity skin extracts. Skin comprises higher proportion of solid and ash content and lower proportion of water content than the fillet. Leaves of 2 year ages plants contained higher proportion of solid content than both of the 3 year and 1 year ages plants leaves. The 80% ethanol extract of the skin showed antimicrobial sensitivity in the order of 3 years > 2 year l> 1year ages of plants. Keywords: Aloe indica, Mineral contents, Fatty acid analysis, Antimicrobial sensitivity. Â Â Â doi: 10.3329/bjsir.v43i4.2237 Bangladesh J. Sci. Ind. Res. 43(4), 467-482, 2008